2001
DOI: 10.1002/mpo.1162
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatoblastoma in childhood: Clinical course and therapeutic management of seven patients

Abstract: Pancreatoblastoma is a curable tumor. Examination of serum AFP levels may be useful for diagnosis and to follow the course of the disease. Complete resection is the treatment of choice. However, tumor is often unresectable at diagnosis and preoperative chemotherapy is needed to reduce tumor volume. We suggest a regimen that include cisplatin and doxorubicin. In patients with incompletely resected disease, postoperative radiation may be indicated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
81
0
2

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(86 citation statements)
references
References 32 publications
1
81
0
2
Order By: Relevance
“…Although the benefits of neoadjuvant chemotherapy have yet to be studied in randomised trials, it has demonstrated a survival benefit in a small pediatric series (37). Of six pediatric patients treated with neoadjuvant chemotherapy, five exhibited >50% tumour remission, allowing for complete surgical resection in four of the five patients, the fifth patient underwent a laparotomy, however the tumour remained unresectable due to regional extension, and one patient achieved complete tumour regression (37).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the benefits of neoadjuvant chemotherapy have yet to be studied in randomised trials, it has demonstrated a survival benefit in a small pediatric series (37). Of six pediatric patients treated with neoadjuvant chemotherapy, five exhibited >50% tumour remission, allowing for complete surgical resection in four of the five patients, the fifth patient underwent a laparotomy, however the tumour remained unresectable due to regional extension, and one patient achieved complete tumour regression (37).…”
Section: Discussionmentioning
confidence: 99%
“…Of six pediatric patients treated with neoadjuvant chemotherapy, five exhibited >50% tumour remission, allowing for complete surgical resection in four of the five patients, the fifth patient underwent a laparotomy, however the tumour remained unresectable due to regional extension, and one patient achieved complete tumour regression (37). Therefore, neoadjuvant chemotherapy may have a role in the treatment of adult PB, predominantly in identifying patients with responsive disease, who may be candidates for surgical resection.…”
Section: Discussionmentioning
confidence: 99%
“…При наличии отдаленных метастазов (обычно в печени или скелете) результаты неблагоприятны [11,15,20]. Опубликовано много работ, где химиотерапия, особенно цисплатинсодержащие схемы, приводи-ла к уменьшению опухолевой массы [11,[21][22][23][24][25]. У детей с местнораспространенными панкреато-бластомами в предоперационном периоде исполь-зовался цисплатин и доксорубицин.…”
unclassified
“…У детей с местнораспространенными панкреато-бластомами в предоперационном периоде исполь-зовался цисплатин и доксорубицин. Полученные данные позволили авторам рекомендовать этот режим для неоперабельных опухолей [25]. После проведенной предоперационной химиотерапии, если удается выполнить радикальную операцию, результаты тоже можно считать удовлетворитель-ными [26].…”
unclassified
“…9 Pancreatoblastomas has several similarities with hepatoblastoma, both having associations with Beckwith-Wiedemann. Other differential diagnosis includes large intra-or retroperitoneal mass, such as a neuroblastoma, non-Hodgkin lymphoma, Wilms tumor.…”
mentioning
confidence: 99%